Efecto de las diferentes fuentes de fibra sobre los parámetros productivos de los pollos de carne criados en altura - Agila Córdova, Ronaldo Elizandro (2023)
Feeding in poultry constitutes around 65 to 70% of production costs; under this premise arises the need to evaluate feed alternatives that cover nutritional requirements, increase productive parameters and minimize expenses; the objective of the present research was to estimate the effect of different fiber sources on the productivity parameters of broilers raised at altitude, we used four hundred one-day-old, unsexed broilers of the Cobb 500 genetic line, with an average weight of 43 g; treatments were applied from day eight to day 28 and consisted of T1 (5 %), T2 (18 %), T3 (18 %), T4(18 %) with the inclusion of the different fiber sources such as wheat bran, rice husk and palm kernel, the variables evaluated were PVS, CMD, GMD, feed conversion and mortality, we conducted the statistical analysis with the SAS program, a mixed model of repetitive measures, to determine the difference of averages between treatments we performed the Tukey test, and for mortality, we used the GENMOD procedure of the SAS statistical program. The results showed statistical differences for the variables studied, with a lower index in T3 and T4 concerning the other treatments. Therefore, we concluded that the inclusion of 5% wheat bran generated better results than other sources of fiber due to better assimilation of the feed, obtaining a better productive performance in the birds.